Budget impact analysis of routinely using whole-genomic sequencing of six multidrug-resistant bacterial pathogens in Queensland, Australia. Issue 2 (1st February 2021) - Gordon, Louisa G; Elliott, Thomas M; Forde, Brian; Mitchell, Brett; Russo, Philip L; Paterson, David L; Harris, Patrick N A
Abstract : Objective: To predict the cost and health effects of routine use of whole-genome sequencing (WGS) of bacterial pathogens compared with those of standard of care. Design: Budget impact analysis was performed over the following 5 years. Data were primarily from sequencing results on clusters of multidrug-resistant organisms across 27 hospitals. Model inputs were derived from hospitalisation and sequencing data, and epidemiological and costing reports, and included multidrug resistance rates and their trends. Setting: Queensland, Australia. Participants: Hospitalised patients. Interventions: WGS surveillance of six common multidrug-resistant organisms ( Staphylococcus aureus, Escherichia coli, Enterococcus faecium, Klebsiella pneumoniae, Enterobacter sp and Acinetobacter baumannii ) compared with standard of care or routine microbiology testing. Primary and secondary outcomes: Expected hospital costs, counts of patient infections and colonisations, and deaths from bloodstream infections. Results: In 2021, 97 539 patients in Queensland are expected to be infected or colonised with one of six multidrug-resistant organisms with standard of care testing. WGS surveillance strategy and earlier infection control measures could avoid 36 726 infected or colonised patients and avoid 650 deaths. The total cost under standard of care was A170.8 million in 2021. WGS surveillance costs an additional A26.8 million but was offset by fewer costs for cleaning, nursing, personal protective equipment, shorter hospital stays and antimicrobials to produce an overall cost savings of 30.9 million in 2021. Sensitivity analyses showed cost savings remained when input values were varied at 95% confidence limits. Conclusions: Compared with standard of care, WGS surveillance at a state-wide level could prevent a substantial number of hospital patients infected with multidrug-resistant organisms and related deaths and save healthcare costs. Primary prevention through routine use of WGS is an investment priority for the control of serious hospital-associated infections.